Sustainable Survival for adolescents living with HIV: Do SDG-aligned provisions reduce potential mortality risk? - Cluver, L; Pantelic, M; Orkin, M; Toska, E; Medley, S; Sherr, L (Wiley, 2018)
Introduction The Sustainable Development Goals (SDGs) present a groundbreaking global development agenda to protect the most vulnerable. Adolescents living with HIV in Sub-Saharan Africa continue to experience extreme health vulnerabilities, but we know little about the impacts of SDG-aligned provisions on their health. This study tests associations of provisions aligned with five SDGs with potential mortality risks. Methods Clinical and interview data were gathered from N = 1060 adolescents living with HIV in rural and urban South Africa in 2014 to 2015. All ART-initiated adolescents from 53 government health facilities were identified, and traced in their communities to include those defaulting and lost-to-follow-up. Potential mortality risk was assessed as either: viral suppression failure (1000+ copies/ml) using patient file records, or adolescent self-report of diagnosed but untreated tuberculosis or symptomatic pulmonary tuberculosis. SDG-aligned provisions were measured through adolescent interviews. Provisions aligned with SDGs 1&2 (no poverty and zero hunger) were operationalized as access to basic necessities, social protection and food security; An SDG 3-aligned provision (ensure healthy lives) was having a healthy primary caregiver; An SDG 8-aligned provision (employment for all) was employment of a household member; An SDG 16-aligned provision (protection from violence) was protection from physical, sexual or emotional abuse. Research partners included the South African national government, UNICEF and Pediatric and Adolescent Treatment for Africa. Results 20.8% of adolescents living with HIV had potential mortality risk – i.e. viral suppression failure, symptomatic untreated TB, or both. All SDG-aligned provisions were significantly associated with reduced potential mortality risk: SDG 1&2 (OR 0.599 CI 0.361 to 0.994); SDG 3 (OR 0.577 CI 0.411 to 0.808); SDG 8 (OR 0.602 CI 0.440 to 0.823) and SDG 16 (OR 0.686 CI 0.505 to 0.933). Access to multiple SDG-aligned provisions showed a strongly graded reduction in potential mortality risk: Among adolescents living with HIV, potential mortality risk was 38.5% with access to no SDG-aligned provisions, and 9.3% with access to all four. Conclusions SDG-aligned provisions across a range of SDGs were associated with reduced potential mortality risk among adolescents living with HIV. Access to multiple provisions has the potential to substantially improve survival, suggesting the value of connecting and combining SDGs in our response to paediatric and adolescent HIV